Basic marketing : a managerial perspective - Quester, Pascale G (Sydney McGraw Hill, 2001)
Prepares students for taking an active part in the business world by providing them with a strategy for learning and for practice. The new edition has an even stronger emphasis on strategy planning and marketing decision process. There are over 40 mew cases drawn from the entire Asia-Pacific region.
Age Group: Adult
Audience: Tertiary students.
v.1 Text -- v.2 Learning aid.
Includes bibliographical references
Previous ed.: Basic marketing : a managerial approach, 1997.
Includes index.